(untitled) (Colombia Medica, 2006)
Objective: This paper deals with the correlation between distress in battered women and abuse by their mates. Materials and methods: The sample involves 199 women referring their domestic violence cases to family legal agencies in Medellín, Colombia, during 2003. To measure distress the Derogatis Distress Symptom List (SCL-90R) was used. To measure abuse the Strauss and Gelles Conflict Tactics Scale (SCT) was used. The age of the women was between 16 and 72 yo. Average age 35.47 years. Standard deviation 10.00. Results: According to SCL-90R nine primary symptoms dimensions and three global distress indexes were calculated.Those are superior (p< 0.0001), than the reference values established by Derogatis for non-patient women and close to the women’s psychiatric patients ambulatory treatment. The total violence index and the severity of the injuries index were calculated and a correlation was found with the three global indexes and the nine symptom dimensions in the SCL-90R. The posttraumatic stress syndrome was found in 54.2% of the women that presented more frequent major agressions, with or without sexual attack, respectively p 0.091 and 0.027. Conclusions: Studies on domestic violence indicate a complex relationship between stress and battering. Both are risk factors for women’s health and quality of life. The application of instruments could enhance the opportunities for communication with the women and increases the recognition of the problem and its consequences.